IMPLEMENTASI BIROKRASI DALAM PENGUATAN FUNGSI FORKOPIMDA PADA PENANGANAN ISU KEKERASAN DI KOTA TUAL - Marsya Zusrieka; Najla Dara Ayunda; Chifra Zeila Pramesyanti; Andzi Salwa Salsabila; Muhammad Prakoso Aji (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The rate of cesarean section has increased significantly and has become a major concern in maternal healthcare services. Therefore, Abstract: This study aims to analyze the application of bureaucracy in strengthening the functions of the Regional Leadership Coordination Forum (Forkopimda) in addressing violence in Tual City. The method used is a qualitative approach based on a literature review, utilizing secondary data obtained from previous literature, official documents, reliable websites, online news, and prior research. This study employs Max Weber’s theory of bureaucratic principles as well as the concept of collaborative policing. The findings indicate that Forkopimda in Tual City has successfully coordinated various government agencies and security forces, although coordination challenges and human resource limitations persist. The application of bureaucratic principles, such as clear division of tasks, hierarchical structure, and cross-sectoral coordination, has proven effective in preventing and addressing violence. However, institutional capacity building and community engagement are still needed to foster greater social stability and more effective violence management.